Flow instability in a volute-free centrifugal fan subjected to non-axisymmetric pre-swirl flow from upstream bended inflow tube. (June 2022) - Liu, Zhengfeng; Yang, Hui; He, Haijiang; Yu, Peiquan; Wei, Yikun; Zhang, Wei
The characteristics of internal flow and performance of a centrifugal fan is greatly dependent on the inflow pattern. As the fan is subjected to incoming flow from an upstream tube, the size and geometry of the tube affect the three-dimensional motion of local flow and possibly degrades the aerodynamic performance of the fan. In this work, we performed a numerical investigation on the internal flow in a centrifugal fan subjected to incoming flow from an upstream bended inflow tube of various radii using the steady and unsteady Reynolds-averaged Navier-Stokes (RANS and URANS) simulation approaches. The effects of the non-axisymmetric pre-swirl flow generated due to the curvature of the bended inflow tube are demonstrated by analyzing the internal flow characteristics of the fan, including the spatial distributions and temporal variations of pressure field and streamlines, pressure fluctuations in the upstream tube, the inflow and outflow sections of the impeller, and the circumferential distributions of velocity and pressure in the impeller. The numerical results reveal that as the inflow tube is curved with larger curvature (smaller radius of the bended section), the pre-swirl inflow is strong and deteriorates the static pressure rise and static pressure efficiency of the centrifugal fan more remarkably, and the circumferential non-uniformity of pressure and velocity distributions appears inside of the channels of the fan. As the radius of the bended section increases, the instability of the internal flow gets more pronounced, as represented by the stronger pressure fluctuations at the inflow and outflow sections. The prediction capabilities of RANS and URANS approaches are also analyzed based on the numerical data and we found that the latter is more reliable in predicting the performance of the fan.